Pengaruh Promosi, Potongan Harga Dan Pelayanan Terhadap Volume Penjualan (Studi Pada PT. Sumber Alfaria Trijaya) Alfamart - Ahmad Refaldi; Kurniaty Kurniaty; Abdul Kadir (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze: (1) The effect of promotions, discounts and services at PT. Sumber Alfaria Trijaya (Alfamart) (2) Sales Volume (Study at PT. Sumber Alfaria Trijaya (Alfamart). The research design is a quantitative study and uses several data collection methods which are collected directly by the researcher himself and obtained from the source to be specifically examined and recorded as well as those sourced from records at the company or other sources, namely by holding a library stadi, in the form of documents, notes and published and unpublished reports that have been compiled. The results showed 1) Promotion (X1) partially had a significant effect on sales volume (Y). Discounts (X2) partially have no significant effect on sales volume (Y). Service (X3) partially has no significant effect on sales volume (Y). The results of the F test prove that the variables Promotion (X1), Discounts (X2) and Service (X3) simultaneously have a significant effect on the Sales Volume variable (Y). This is because if the Promotion is comparable to the Discounted Prices and Services performed, it will automatically increase sales volume.